Fatty Acid Substitutions Modulate the Cytotoxicity of Puwainaphycins/Minutissamides Isolated from the Baltic Sea Cyanobacterium Nodularia harveyana UHCC-0300 - Saurav, Kumar; Caso, Alessia; Urajová, Petra; Hrouzek, Pavel; Esposito, Germana; Delawská, Kateřina; Macho, Markéta; Hájek, Jan; Cheel, José; Saha, Subhasish; Divoká, Petra; Arsin, Sila; et al. (ACS omega, 2022)
Puwainaphycins (PUW) and minutissamides (MIN) are structurally homologous cyclic lipopeptides that exhibit high structural variability and possess antifungal and cytotoxic activities. While only a minor variation can be found in the amino acid composition of the peptide cycle, the fatty acid (FA) moiety varies largely. The effect of FA functionalization on the bioactivity of PUW/MIN chemical variants is poorly understood. A rapid and selective liquid chromatography-mass spectrometry-based method led us to identify 13 PUW/MIN (1-13) chemical variants from the benthic cyanobacterium Nodularia harveyana strain UHCC-0300 from the Baltic Sea. Five new variants identified were designated as PUW H (1), PUW I (2), PUW J (4), PUW K (10), and PUW L (13) and varied slightly in the peptidic core composition, but a larger variation was observed in the oxo-, chloro-, and hydroxy-substitutions on the FA moiety. To address the effect of FA substitution on the cytotoxic effect, the major variants (3 and 5-11) together with four other PUW/MIN variants (14-17) previously isolated were included in the study. The data obtained showed that hydroxylation of the FA moiety abolishes the cytotoxicity or significantly reduces it when compared with the oxo-substituted C18-FA (compounds 5-8). The oxo-substitution had only a minor effect on the cytotoxicity of the compound when compared to variants bearing no substitution. The activity of PUW/MIN variants with chlorinated FA moieties varied depending on the position of the chlorine atom on the FA chain. This study also shows that variation in the amino acids distant from the FA moiety (position 4-8 of the peptide cycle) does not play an important role in determining the cytotoxicity of the compound. These findings confirmed that the lipophilicity of FA is essential to maintain the cytotoxicity of PUW/MIN lipopeptides. Further, a 63 kb puwainaphycin biosynthetic gene cluster from a draft genome of the N. harveyana strain UHCC-0300 was identified. This pathway encoded two specific lipoinitiation mechanisms as well as enzymes needed for the modification of the FA moiety. Examination on biosynthetic gene clusters and the structural variability of the produced PUW/MIN suggested different mechanisms of fatty-acyl-AMP ligase cooperation with accessory enzymes leading to a new set of PUW/MIN variants bearing differently substituted FA.